Dynamic behavior, stochasticity and enviromental heterogeneity in Tribolium castaneum - Romão, Ana Rita Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In this study we analyzed the influence of demographic parameters on the population dynamics of Tribolium castaneum, combining empiricism and population theory to analyze the different effects of environmental heterogeneity, by employing Ricker models, designed to study a two-patch system taking into account deterministic and stochastic analysis. Results were expressed by bifurcation diagrams and stochastic simulations. Dynamic equilibrium was widely investigated with results suggesting specific parametric spaces in response to environmental heterogeneity and migration. Population equilibrium patterns, synchrony and persistence in T. castaneum were discussed

Neste estudo analisamos a influência de parâmetros demográficos na dinâmica da população do Trbibolium castaneum, combinando empriricismo e teoria de populações para analisar os diferentes efeitos da heterogeneidade ambiental, empregando modelos de Ricker, designados ao estudo de um sistema de dois patches levando em conta análises determinísticas e estocásticas. Os resultados foram expressos através de diagramas de bifurcação e simulações estocásticas. O equilíbrio dinâmico foi amplamente investigado com resultados sugerindo espaços paramétricos específicos em resposta à heterogeneidade ambiental e à migração. Padrões de equilíbrio de população, sincronia e persistência em T. castaneum foram discutidos
Comportamento dinâmico, estocaticidade e heterogeneidade ambiental em Tribolium castaneum
Keywords: Genetica de populações; Zoologia; Heterogeneidade